Analisis Tingkat Kebisingan Akibat Lalu Lintas Pada Kawasan Perkantoran dan Pendidikan di Kecamatan Kota Utara Kota Gorontalo - D. Fortuna; M. Mahmud; Y. Kadir (Civil Engineering Department, Tadulako University, 2022)
Increased traffic volume can result in environmental issues such as noise or noise pollution. The purpose of this study is to analyze the noise levels in the office and educational areas in Kota Utara District, Gorontalo City, using a traffic noise prediction calculation model and to analyze the comparative value of noise levels based on the prediction calculation model and quality standards according to KEP-48/MENLH/11/1996. The location of this study is spread over several points, namely in Kampus STIKES Bina Mandiri Gorontalo, in front of Kantor Kejaksaan Tinggi Gorontalo, and in front of Kantor Imigrasi TPI Kelas I Gorontalo. The method used in this study is an empirical method with a prediction model for traffic noise prediction.The results showed that the highest noise levels on Monday and Thursday occurred in the Kampus STIKES Bina Mandiri Gorontalo area with a noise intensity of 65.71 dB (A) and 64.71 dB (A). The highest noise level on Saturday occurred in front of Kantor Kejaksaan Tinggi Gorontalo with a noise intensity of 65.12 dB (A). According to a comparison of the results of the analysis and the quality standard according to KEP-48/MENLH/11/1996, the average noise level in the Kampus STIKES area has exceeded the quality standard value for the educational area, which is 55 dB (A). The noise level in front of Kantor Kejaksaan Tinggi Gorontalo on Saturday at 07.00–08.00 WITA shows that the noise intensity has exceeded the quality standard for office areas, which is 65 dB (A). Meanwhile, the noise level in front of Kantor Imigrasi on average still meets the quality standards required for office areas.